HOW TO MANAGE CLASSES OF INTERNATIONAL STUDENTS IN SOUTHERN THAILAND: STUDY OF ALAUDDIN UNIVERSITY TRAINEES - Thulfitrah B., Nurlathifah; Ahmad, La Ode Ismail; Arifin, Nur (Jurnal Diskursus Islam, 2022)
This study describes the effect of microteaching learning to manage classes of international trainees of Tarbiyah and the Teacher Training Faculty. This quantitative type of research was conducted on 13 students with a non-probability sampling technique, namely a saturated sample, where all members of the population were sampled using a questionnaireand documentation checklist as a research instrument, to obtain data that was processed and analyzed by statistical techniques, both descriptive statistics, and inferential statistics. Through data analysis, it was concluded that the results of testing data on the effect of microteaching learning to manage classes of international trainees were indicated by a low category or a weak relationship of 0.275 and significant at 4.179 with a contribution percentage of 7.6. %, while the remaining 92.4% is influenced by other variables. The ability to manage classes of the international trainee can be applied well through microteaching learning according to existing theories, but because the results have a low/not strong effect, it is necessary to improve or look for other factors that can improve the teaching practice abilities of an international trainee.